Does the use of upper leg compression garments aid performance and reduce post-race Delayed Onset Muscle Soreness (DOMS)? - Kabongo, Ken (Division of Exercise Science and Sports Medicine, 2022)
Introduction: Despite the lack of scientific knowledge on the physiological and biomechanical effects of wearing compression garments, there has been an increase in the use of these garments in endurance running. The purpose of this study was to compare the performance, pain and thigh circumference changes in endurance runners using upper leg compression garments while competing against runners who did not use compression garments in the same marathon race. Methods: A randomised controlled intervention study was conducted in endurance runners (n=18) participating in the 2019 Winelands Marathon (42.2km). The compression garment group (n=10) participated in the race wearing upper leg compression garments while the control group (n=8) did not. Participants in the compression garment group only wore the compression garments during the marathon. Various outcome measures of perceived exercise-induced muscle damage (EIMD) and running performance were assessed three days before, immediately post-race and two days post-race. Three days prior to the race, mid-thigh circumference measurements were performed. Immediately post-race, mid-thigh circumference measurements, Visual Analogue Scale (VAS) pain ratings and Likert scale for determination of muscle soreness were assessed and race performance times were recorded. Two days post-race, mid-thigh circumference measurements, VAS pain rating and Likert scale for determination of muscle soreness were repeated. Results: VAS pain ratings for hamstring (compression garment 2.50 vs control group 4.00) (p=0.04), knee flexion (compression garment 2.50 vs control group 5.00) (p=0.02) and hip extension (compression garment 2.50 vs control group 4.00) (p=0.04) had a statistically significant difference between the compression garment and control group immediately post-race. VAS pain ratings for hamstring (compression garment 0.00 vs control group 1.00) (p=0.04), knee flexion (compression garment 1.00 vs control group 2.00) (p=0.02) and hip extension (compression garment 1.00 vs control group 2.50) (p=0.04) had a statistically significant difference between the compression garment and control group two days post-race. There were no statistically significant differences in any other outcome measures (i.e. Likert scale for determination of muscle soreness, mid-thigh circumference and race performance) between the compression garment and control group. Conclusion: The use of upper leg compression garments is a recovery ergogenic aid which improves VAS pain ratings post-race. The results suggest that upper leg compression garments have a protective effect on the hamstring muscle in runners in the recovery phase. However, since a runner would be in a recovery phase after a marathon, a minor difference would be of little practical advantage since, importantly, there was no statistically significant differences in race performance and thigh circumference measures.